International situations and their impact on the balance of power (1884-1914م) (Journal of Human Sciences, 2023)
This The period extends from 1884 AD، which was the year the Berlin conference was held، until 1914 AD when the First World War took place. It is considered one of the important periods because of the events it witnessed، and its results left a lasting impact and resonance. This impact was not at the local level in which it occurred، but even at the global level which changed in several aspects. Perhaps one of the most important aspects was the balance of power. From this logic، the researchers chose this topic، but through it the researchers obtained the desired results. It is divided into an introduction، a preface، three topics، a conclusion، and a list of sources and references that were relied upon in this study. The topics are:Preface: Through it، the researcher will provide an overview of the conditions before 1884.First topic: The Berlin Conference 1884-1885 and its most prominent results.Second topic: International alliances 1873-1907 AD and their impact on the characteristics of power.Third topic: The political situation from 1905-1914 AD and the most important crises that occurred and what resulted from them.